'The grievances from toleration': Scotland heading towards the Enlightenment. (2nd April 2020) - Maurer, Christian
ABSTRACT: In this article, I analyse some pre-Humean arguments for and against tolerance by early eighteenth-century Scottish philosophers and theologians. I present these in dialogue with the Confession of Faith, which constituted the central doctrinal pillar of the Presbyterian Church of Scotland. The Kirk viewed tolerance rather suspiciously as a danger for its unity, and if the Confession asserted liberty of conscience against the Catholics, it insisted nevertheless on rigid boundaries. This created tensions which the theologians John Simson and Archibald Campbell sought to exploit when they were attacked by Committees for Purity of Doctrine for suspicion of heresy. Simson's and Campbell's arguments for toleration revolved around issues of liberty of conscience, scripture interpretation and the necessity of open debate for the moral progress of mankind. George Turnbull and Francis Hutcheson, then, insisted on a moral core of religion and on limitations of the Church's power. They showed more optimism than David Hume regarding our moral resources to overcome religion's corruptive potential, under the condition that we are properly guided.